ZBTB10 as a potential prognosis biomarker and correlates with the tumor immune microenvironment in stomach adenocarcinoma - Yingdi Jiang; Fuhua Han; Lu Dai; Shali Qiu; Yanjie Zhou; Ke Wang; Jiang Lin (BMC Gastroenterology)
Abstract Background ZBTB10 is a member of the zinc finger and bric-a-brac/tramtrack/broad (ZBTB) domain-containing protein family, reported to be associated with tumorigenesis and progression. However, its specific roles in oncogenesis, prognosis, and immune infiltration in stomach adenocarcinoma (STAD) remain to be elucidated. Methods We analyzed ZBTB10 mRNA and protein expression profiling in STAD tissues using various bioinformatics tools, including TIMER2, GEO, Human Protein Atlas (HPA) databases, and R software. Survival analysis was performed through the Kaplan–Meier plotter. UALCAN and TCGA databases were used to evaluate the association of ZBTB10 expression with clinicopathological characteristics. Genetic alterations of ZBTB10 in human tumor samples were analyzed using the cBioPortal database. The correlation between ZBTB10 expression and immune cell infiltration was assessed using the TISIDB and CIBERSORT algorithms. Gene Set Enrichment Analysis (GSEA) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were applied to investigate the potential mechanism of ZBTB10 in STAD. Additionally, in vitro assays such as CCK-8, colony formation, and wound healing assays were performed to determine the biological role of ZBTB10 in STAD cells. Multiple immunohistochemistry (mIHC) was applied to characterize the association between immune cell infiltration and ZBTB10 expression in STAD tumor tissues. Results Overall, ZBTB10 was differentially expressed in STAD compared to adjacent normal tissues, and higher ZBTB10 expression correlated with poorer overall survival (OS). Furthermore, GSEA and KEGG analysis suggested that ZBTB10 was predominantly involved in focal adhesion, PI3K-Akt signaling, and MAPK signaling pathways, suggesting its potential role in promoting tumor growth and progression. Moreover, based on the CIBERSORT algorithm, the expression of ZBTB10 was positively related to the levels of B cells, CD4 + T cells, M1 macrophages, and neutrophil cells. Meanwhile, ZBTB10 expression appeared to be negatively associated with tumor mutation burden (TMB) and microsatellite instability (MSI) in STAD, both of which influenced the efficacy of tumor immunotherapy. In vitro experiments demonstrated that ZBTB10 knockdown significantly inhibited tumor cell proliferation and invasion, and organoid area in STAD cell lines. The immune cell signature of CD45 was more prevalent with ZBTB10 expression in tumor tissue sections compared to adjacent normal tissues from STAD patients. Conclusions Upregulated ZBTB10 is significantly correlated with poor survival outcomes and immune infiltration in STAD, revealing that ZBTB10 may serve as a promising prognostic biomarker and a potential target for immunotherapy in STAD.